MiR-142-5p/FAM134B Axis Manipulates ER-Phagy to Control PRRSV Replication - Guan, Kaifeng; Su, Qiuju; Kuang, Kailin; Meng, Xiangge; Zhou, Xiang; Liu, Bang (Frontiers in Immunology, 2022)
Porcine reproductive and respiratory syndrome virus (PRRSV) can replicate its RNA genome in endoplasmic reticulum (ER) and utilize ER to facilitate its assembly and maturation. To maintain ER homeostasis, host cells initiate reticulophagy (known as ER-phagy) to effectively digest the stressed ER. In this study, we found that PRRSV infection subverted ER-phagy by down-regulating ER-phagy receptor FAM134B. PRRSV-induced miR-142-5p directly targeted FAM134B and significantly promoted PRRSV replication. Meanwhile, siRNA-mediated depletion of FAM134B protein and overexpression of FAM134B mutant protein significantly disrupted ER-phagy and facilitated PRRSV replication. Furthermore, our results showed that FAM134B-mediated ER-phagy activated type I interferon signaling to inhibit PRRSV replication. Overall, this study reveals the important role of ER-phagy in PRRSV replication in a FAM134B-dependent manner. Our findings provide an insight into the pathogenesis of PRRSV and offer theoretical basis for further development of antiviral therapeutic targets.